2020
DOI: 10.1140/epjc/s10052-020-8355-2
|View full text |Cite
|
Sign up to set email alerts
|

Dust content solutions for the Alcubierre warp drive spacetime

Abstract: The Alcubierre metric is a spacetime geometry where a massive particle inside a spacetime distortion, called warp bubble, is able to travel at velocities arbitrarily higher than the velocity of light, a feature known as the warp drive. This is a consequence of general relativity, which allows for global superluminal velocities but restricts local speeds to subluminal ones as required by special relativity. In this work we solved the Einstein equations for the Alcubierre warp drive spacetime geometry considerin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…In this paper we generalize the results obtained in Ref. [19] by following the next logical step, that is, investigating the perfect fluid as EMT source for the Alcubierre metric. We also propose a slightly generalized perfect fluid EMT, called here the parametrized perfect fluid (PPF), in order to produce a tentatively more flexible model such that the pressure may have different parameter values.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…In this paper we generalize the results obtained in Ref. [19] by following the next logical step, that is, investigating the perfect fluid as EMT source for the Alcubierre metric. We also propose a slightly generalized perfect fluid EMT, called here the parametrized perfect fluid (PPF), in order to produce a tentatively more flexible model such that the pressure may have different parameter values.…”
Section: Introductionmentioning
confidence: 71%
“…For the perfect fluid EMT solutions we found that two out of four subcases turn out to be the dust solution of Ref. [19] where both the matter density and the pressure vanish, but the Burgers equation also appears as a result of the solutions of the Einstein equations [29][30][31]. Two other subcases, however, indicate that warp speeds are possible with positive matter density, but at the cost of a complex solution for the warp metric regulating function.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Loup expanded Natário's work to encompass a global acceleration [4,5]. Finally, recent research has investigated the Einstein equations for the Alcubierre spacetime with a dust matter distribution as its source [13].…”
Section: Introductionmentioning
confidence: 99%